2018
DOI: 10.1080/23273798.2018.1446542
|View full text |Cite
|
Sign up to set email alerts
|

Widening agreement processing: a matter of time, features and distance

Abstract: Existing psycholinguistic models typically describe agreement relations as monolithic phenomena amounting to mechanisms that check mere feature consistency. This eye-tracking study aimed at widening this perspective by investigating the time spent reading subject-verb (number, person) and adverb-verb (tense) violations on an inflected verb during sentence comprehension in Spanish. Results suggest that (i) distinct processing mechanisms underlie the analysis of subject-verb and adverb-verb relations, (ii) the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 46 publications
3
24
0
Order By: Relevance
“…While experimental studies overall agree that the response to agreement violations is stronger when person, rather than number is involved, they diverge on whether qualitative (Mancini et al, 2011(Mancini et al, , 2017Biondo et al, 2018) or quantitative (Zawiszewski et al, 2016) differences emerge between these two features. Ackema and Neeleman's analysis proposes that the type of agreement controller and the distinct feature sets that pronouns and regular noun phrases (NPs) carry can reconcile these apparently contradicting results.…”
Section: Distinct Features Distinct Mechanisms? Against Features As Uniform Constructsmentioning
confidence: 95%
See 1 more Smart Citation
“…While experimental studies overall agree that the response to agreement violations is stronger when person, rather than number is involved, they diverge on whether qualitative (Mancini et al, 2011(Mancini et al, , 2017Biondo et al, 2018) or quantitative (Zawiszewski et al, 2016) differences emerge between these two features. Ackema and Neeleman's analysis proposes that the type of agreement controller and the distinct feature sets that pronouns and regular noun phrases (NPs) carry can reconcile these apparently contradicting results.…”
Section: Distinct Features Distinct Mechanisms? Against Features As Uniform Constructsmentioning
confidence: 95%
“…A prolific strand of experimental research has been also devoted to investigating whether features' distinct representational properties have a processing reflex, of which the person-number dissociation hypothesis has been one of the main testing grounds (Nevins et al, 2007;Silva-Pereyra and Carreiras, 2007;Mancini et al, 2011Mancini et al, , 2017Zawiszewski et al, 2016;Biondo et al, 2018 to name a few). Existing findings attributed qualitative differences in their processing to the different interpretive properties that characterize the two types of agreement: the link to discourse participant roles that is necessary to interpret 1st, 2nd, or 3rd person (a speaker, an addressee or a non-active participant), but not the singularity or the plurality of the individuals involved in the speech event.…”
Section: Distinct Features Distinct Mechanisms? Against Features As Uniform Constructsmentioning
confidence: 99%
“…This prediction would be in line with previous eye-tracking studies investigating the processing of temporal violations. In particular, Biondo et al (2018) tested adverb-verb violations by using an eye-tracking-while-reading paradigm, in Spanish. Their results showed that when the adverb and verb were separated by a subject NP (as in the current study), temporal violations gave rise to longer reading times compared to the control condition, both in first-pass and total time measures.…”
Section: The Current Studymentioning
confidence: 99%
“…By tracking eye movements during the reading of sentences where the temporal specifications of adverbs and verbs were manipulated to match or mismatch, we were able to observe the time course of temporal information processing during sentence reading. Based on previous ERP and eye-tracking studies (Baggio, 2008;Biondo et al, 2018), we expected increased reading times at a verb whose tense mismatched the temporal specification of the preceding adverb, compared to a verb with matching information. In line with this prediction, we showed that a temporal mismatch between adverb and verb generates reading disruptions already beginning from the first pass through the verb.…”
Section: Time Course Of Temporal Processing During Sentence Readingmentioning
confidence: 99%
“…This is sometimes characterized as a LAN-P600 complex (Steinhauer and Ullman, 2002; Baggio, 2008), sometimes as an N400-P600 complex (Dillon et al, 2012; Qiu and Zhou, 2012). More recently, it has also been shown that when a temporal mismatch occurs between a deictic temporal adverb and a distal verb (e.g., Yesterday afternoon the tired traveler ∗ will come/came back home ) longer reading times are found compared to the correct control condition, both in early and late eye-tracking measures (Biondo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%